INVESTIGATING THE MEDIATING ROLE OF SELF-EFFICACY IN THE RELATIONSHIP BETWEEN CONTINUING EDUCATION AND JOB PERFORMANCE AMONG SAUDI ARABIAN NURSES - Amal Nawaf Alanazi, Huda Nawaf Alanazi , Budor Arrak Aldhaferi, Fatma Fares Albnaqi, Naimah Naif Alsalem, Nada Hadiri Alshridi (Chelonian Research Foundation, 2022)
Continuing education plays a crucial role in the professional development and performance of nurses. However, the mechanisms through which continuing education influences job performance remain understudied, particularly in the context of Saudi Arabian healthcare. This study aimed to investigate the mediating role of self-efficacy in the relationship between continuing education and job performance among Saudi Arabian nurses. A cross-sectional survey design was employed, and data were collected from a sample of 300 nurses working in various healthcare settings in Saudi Arabia. Structural equation modeling (SEM) was used to test the hypothesized mediation model. The results revealed that continuing education had a significant positive effect on both self-efficacy and job performance. Moreover, self-efficacy partially mediated the relationship between continuing education and job performance. The findings suggest that investing in continuing education programs that enhance nurses' self-efficacy can lead to improved job performance and ultimately contribute to better patient outcomes. Healthcare organizations and policymakers should prioritize the provision of effective continuing education opportunities and foster a supportive learning environment to promote the professional growth and performance of nurses in Saudi Arabia. Keywords: continuing education, self-efficacy, job performance, nurses, Saudi Arabia